2022
DOI: 10.3389/fmicb.2022.967545
|View full text |Cite
|
Sign up to set email alerts
|

Entner-Doudoroff pathway in Synechocystis PCC 6803: Proposed regulatory roles and enzyme multifunctionalities

Abstract: The Entner-Doudoroff pathway (ED-P) was established in 2016 as the fourth glycolytic pathway in Synechocystis sp. PCC 6803. ED-P consists of two reactions, the first catalyzed by 6-phosphogluconate dehydratase (EDD), the second by keto3-deoxygluconate-6-phosphate aldolase/4-hydroxy-2-oxoglutarate aldolase (EDA). ED-P was previously concluded to be a widespread (∼92%) pathway among cyanobacteria, but current bioinformatic analysis estimated the occurrence of ED-P to be either scarce (∼1%) or uncommon (∼47%), de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Our results thus strongly support that the ED pathway is incomplete in S. elongatus with the KDPG aldolase participating in respiration through its alternative decarboxylation activity. This is also consistent with the findings that the KDPG aldolase is much more prevalent than 6PGDH in cyanobacteria 18 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results thus strongly support that the ED pathway is incomplete in S. elongatus with the KDPG aldolase participating in respiration through its alternative decarboxylation activity. This is also consistent with the findings that the KDPG aldolase is much more prevalent than 6PGDH in cyanobacteria 18 .…”
Section: Discussionsupporting
confidence: 92%
“…6). A recent bioinformatics study analyzed the possible cooccurrence of four glycolytic pathways (EMP, ED, OPP, and phosphoketolase) in cyanobacteria and found that the phosphoketolase and OPP pathways had the highest co-occurrence probability of 84.8% compared to all other combinations 18 , supporting the OPP-phosphoketolase route in the dark during cyanobacterial diel light/dark growth. In addition, phosphoketolase exists in other eukaryotes such as diatom (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Early metabolic studies in Entamoeba histolytica 34 , Aspergillus niger 35 , and Penicillium notaturn 36 suggested it was also a significant metabolic route in unicellular or filamentous eukaryotes (reviewed in 2 ). More recently, the enzymatically similar DHAD class of dehydratases from the BCAA pathway has been implicated in the ED pathway, leading to speculation that the ED pathway operates in plants and diatoms [11][12][13] . Based on biochemical characterization of DHAD and EDD substrate specificity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their common evolutionary origin and high degree of amino acid similarity, DHADs and EDDs have been treated collectively in phylogenetic analyses aimed at understanding the natural distribution of the ED pathway 11 . The assumption that they have overlapping substrate specificities and biochemical functions 12 has led to the conclusion that a functional ED pathway operates in flowering plants, mosses, ferns 11 , and diatoms 13 in addition to prokaryotes 4 . Bacteria possess both types of dehydratase, but in plants a definitive physiological role has thus far only been established for DHAD 14 .…”
Section: Introductionmentioning
confidence: 99%